2017
DOI: 10.1038/gim.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

The collective impact of rare diseases in Western Australia: an estimate using a population-based cohort

Abstract: Purpose:It has been argued that rare diseases should be recognized as a public health priority. However, there is a shortage of epidemiological data describing the true burden of rare diseases. This study investigated hospital service use to provide a better understanding of the collective health and economic impacts of rare diseases.Methods:Novel methodology was developed using a carefully constructed set of diagnostic codes, a selection of rare disease cohorts from hospital administrative data, and advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
114
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(123 citation statements)
references
References 25 publications
4
114
1
4
Order By: Relevance
“…The 2% of the population affected by rare diseases accounted for 4.6 to 10.5% of total hospitalization expenditures. 3 These results affirm previous findings. Using codes that largely overlap with the codes used by Walker et al, 3 Yoon et al 5 reported that, in a pediatric population from two states in the United States comprising patients with hospital codes for birth defects and genetic diseases, approximately 2.5% accounted for 9 to 12% of pediatric hospital admissions and 16 to 28% of total costs.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…The 2% of the population affected by rare diseases accounted for 4.6 to 10.5% of total hospitalization expenditures. 3 These results affirm previous findings. Using codes that largely overlap with the codes used by Walker et al, 3 Yoon et al 5 reported that, in a pediatric population from two states in the United States comprising patients with hospital codes for birth defects and genetic diseases, approximately 2.5% accounted for 9 to 12% of pediatric hospital admissions and 16 to 28% of total costs.…”
supporting
confidence: 90%
“…In this issue of Genetics in Medicine , Walker et al 3 describe a meticulous attempt to make the collective burden of rare diseases more visible. Using 11.5 years of linked statewide administrative databases in Western Australia, the authors sought to identify individuals affected with rare diseases.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, by improving certainty of the diagnosis of RD, one could more accurately assess interventions targeted to the reduction of the burden of these conditions. Given the marked disparity between the proportion of the population with RD and their combined health system costs, supporting the need for early diagnosis and intervention has the potential to drive cost savings across the health system (29). …”
Section: Evaluate Effectiveness Accessibility and Quality Of Personmentioning
confidence: 99%